2014
DOI: 10.4244/eijv9i9a184
|View full text |Cite
|
Sign up to set email alerts
|

Gender, TIMI risk score and in-hospital mortality in STEMI patients undergoing primary PCI: results from the Belgian STEMI registry

Abstract: In the Belgian STEMI registry, pPCI-treated women had a higher in-hospital mortality rate even after correcting for TIMI risk score variables. The TIMI risk score was effective in predicting in-hospital mortality but performed slightly better in men. The database was registered with clinicaltrials.gov (NCT00727623).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 33 publications
2
42
1
Order By: Relevance
“…S1). Fourteen studies [19,20,24,28,33,34,[37][38][39]48,[58][59][60][61] (n = 33,380) reported adjusted effect estimates for in-hospital mortality. A meta-analysis using multivariate adjusted effect estimates showed higher mortality in women as compared to men [RR: 1.31, 95% CI: 1.08-1.65, p = 0.007] (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S1). Fourteen studies [19,20,24,28,33,34,[37][38][39]48,[58][59][60][61] (n = 33,380) reported adjusted effect estimates for in-hospital mortality. A meta-analysis using multivariate adjusted effect estimates showed higher mortality in women as compared to men [RR: 1.31, 95% CI: 1.08-1.65, p = 0.007] (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty‐six studies eligible for the meta‐analysis were identified and included, representing 98,778 patients (73,559 men and 25,219 women). The pooled baseline characteristics by sex showed that women were older, were more likely to have hypertension, diabetes mellitus, and hypercholesterolemia.…”
Section: Resultsmentioning
confidence: 99%
“…After adjusting for confounding factors, however, sex differences in mortality were attenuated in most studies, thus, suggesting that this higher baseline cardiovascular risk profile of women might explain the differences in outcome . Other authors, in contrast, reported female sex was independently correlated to a poorer or better prognosis . Moreover, it is unclear if this sex gap is limited to the in hospital period or is sustained over time due to different burden of risk factors, of risk of complications, and of adherence to therapy .…”
Section: Introductionmentioning
confidence: 91%
“…Women with ACS and a high TIMI risk score, which includes clinical, ECG criteria, and biochemical markers, have historically had lower rates of angiography and reperfusion and increased rates of refractory angina and rehospitalization for unstable angina, compared to men 142 . In a more contemporary Belgian cohort of STEMI patients who receive primary PCI, the TIMI risk score was effective in predicting in-hospital mortality for both women and men but performed slightly better in men 143 . Although the GRACE score also does not use sex as a parameter because it was not shown to be a statistically significant predictor of hospital mortality during score development 140 , it may improve risk discrimination in women with the additional parameters of creatinine and cardiac arrest at admission, which may reflect sex differences 144 .…”
Section: Acute Ischemic Heart Diseasementioning
confidence: 90%